Elevated alcohol consumption among geriatric psychiatric in-patients. Issue 4 (August 2020) - Helvik, Anne-Sofie; Engedal, Knut; Johannessen, Aud
Introduction: Although a clear relationship has been established between elevated alcohol consumption and psychiatric problems in old age, there are few descriptions of the prevalence of elevated alcohol consumption in older adults who have been referred to geriatric psychiatric treatment. Aim: To describe the prevalence of self-reported elevated alcohol consumption in men and women referred to geriatric psychiatry wards in Norway, and to explore factors associated with elevated alcohol consumption. Method: This cross-sectional study includes data from a registry of geriatric psychiatry patients aged ≥ 65 years from December 2016 until December 2018. The outcome measure was reported elevated alcohol consumption assessed with the short version of the Alcohol Use Disorders Identification Test (AUDIT-C). The analyses used demographic data as well as a measure of cognitive function, psychiatric diagnosis and use of psychotropic drugs. Results: In total, 367 patients (131, 35.7% men) with a mean ( SD ) age of 74.7 (7.6) years were included. Of these patients, 27% scored above the pre-set cut-off for elevated alcohol consumption according to AUDIT-C (≥ 3 and 4 for women and men, respectively). The prevalence of elevated alcohol did not differ by gender. In adjusted logistic regression analysis, older age, living with someone and use of antidepressants were associated with reduced odds for reporting elevated alcohol consumption ( OR 0.93, 95% CI 0.89–0.96; OR 0.54, 95% CI 0.31–0.97; and 0.54, 95% CI 0.32–0.92, respectively). Conclusion: A relatively high proportion of psychiatric patients aged 65 years or older reported elevated alcohol consumption, regardless of diagnosis. Older age, living with someone and use of antidepressants were associated with lower odds for elevated alcohol consumption.